Collaborative Governance dalam Mewujudkan Taman Maliogoro Sebagai Ikon Wisata Kabupaten Bojonegoro - Hidayat, M Wafiq; Taufiq, Ahmad; Rupiarsieh, Rupiarsieh (Universitas Muhammadiyah Sorong, 2024)
Bojonegoro Regency has wealth in the form of oil and gas resources, as well as a number of tourist destinations that have the potential to be developed to support improving community welfare. This study aims to understand the implementation of Collaborative Governance in Realizing Maliogoro Park as a Tourism Icon of Bojonegoro Regency. This study uses a qualitative approach with a descriptive method, including observation activities, interviews, and documentation collection at the research location. Based on research using five main indicators, it was found that the success of collaboration between stakeholders was influenced by Face to face dialogue, Trust building, Commitment to process, Share understanding, Intermediate outcome as the main key. Now, Malioboro Park has become a favorite destination that has a positive impact on local economic growth. This shows that harmonious collaboration between the Government, Community, and the private sector has a crucial role in encouraging sustainable tourism development